PERCEPTION OF MALAYSIAN PUBLIC ON HERITAGE SITE PRESERVATION - Ashwinia, Mohan (Universiti Malaysia Sarawak, (UNIMAS), 2022)
Preservation of heritage sites has been a dilemma in many countries, including Malaysia. The perceptions of the Malaysian public influence their attitude towards heritage site preservation. This study investigates the perceptions of the Malaysian public on heritage site preservation and the factors influencing their perceptions. This study also examines to what extent the Malaysian people are aware of the importance of preserving heritage sites. An online survey was done through Google form and distributed among the Malaysian public using the online platforms. Analysis shows that the Malaysian public has positive perceptions of heritage site preservation. They also have good knowledge of heritage sites. Factors such as educational level and occupation status have influenced the perceptions of the Malaysian public on heritage site preservation. Overall, they have a very good awareness of the importance of preserving heritage sites. This research is beneficial for future researchers to discover the perceptions and awareness of the Malaysian public on heritage site preservation. If the Malaysian public has negative perceptions, they can identify the factors that influence them and start to implement ways to shape good perceptions among them. Suppose they have good perceptions like in this study. In that case, the future researcher can take initiatives to maintain or increase their good perceptions of heritage site preservation by considering what shapes their good perceptions.